2020
DOI: 10.1007/s40820-020-00540-z
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Wavelength Photosensitive Nano-in-Micro Scaffold Regulates Innate and Adaptive Immune Responses for Osteogenesis

Abstract: The immune response of a biomaterial determines its osteoinductive effect. Although the mechanisms by which some immune cells promote regeneration have been revealed, the biomaterial-induced immune response is a dynamic process involving multiple cells. Currently, it is challenging to accurately regulate the innate and adaptive immune responses to promote osteoinduction in biomaterials. Herein, we investigated the roles of macrophages and dendritic cells (DCs) during the osteoinduction of biphasic calcium phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 62 publications
1
43
0
Order By: Relevance
“…, BMP2, TGFβ, etc. ) [ 58 , 59 ]. In angiogenesis, factors secreted from M2 macrophage, especially platelet-derived growth factor-BB (PDGF-BB), could effectively promote the formation of new blood vessels, thus accelerating the process of bone repair [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…, BMP2, TGFβ, etc. ) [ 58 , 59 ]. In angiogenesis, factors secreted from M2 macrophage, especially platelet-derived growth factor-BB (PDGF-BB), could effectively promote the formation of new blood vessels, thus accelerating the process of bone repair [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells are critical for bone regeneration induced by osteoinductive biomaterials, especially macrophages. It is reported that loss of macrophages impairs tissue regeneration [ 34 ]. Macrophages were highly heterogeneous and plastic, which are responsive to diverse cues and environments.…”
Section: Discussionmentioning
confidence: 99%
“…9 ). Recently, more and more researchers realize that immune responds also play an essential role in bone regeneration [ [55] , [56] , [57] ]. Osteoinductive BCP ceramics might regulate macrophage to secrete related chemokines via ERK signaling pathway, which would accelerate MSCs homing to facilitate bone formation [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the immune response of a biomaterial also determines its osteoinductive effect. Zhao Q et al investigated the roles of macrophages and dendritic cells (DCs) during the osteoinduction of BCP scaffolds, and found that osteoinductive BCP directed M2 macrophage polarization and inhibited DC maturation, resulting in low T cell response and efficient osteogenesis [ 58 ]. Our previous work had been proved that HA bioceramics with nanotopography also had a significant influence on osteoclastogenesis, nanotopography markedly impaired osteoclastic formation and function compared to the ones with the submicron topography, which was further related to its osteoinductive capacity [ 25 ].…”
Section: Discussionmentioning
confidence: 99%